Dracaena marginata biofilter: design of growth substrate and treatment of stormwater runoff. Issue 9 (2nd May 2016) - Vijayaraghavan, K.; Praveen, R.S.
ABSTRACT: The purpose of this research was to investigate the efficiency of Dracaena marginata planted biofilters to decontaminate urban runoff. A new biofilter growth substrate was prepared using low-cost and locally available materials such as red soil, fine sand, perlite, vermiculite, coco-peat and Sargassum biomass. The performance of biofilter substrate was compared with local garden soil based on physical and water quality parameters. Preliminary analyses indicated that biofilter substrate exhibited desirable characteristics such as low bulk density (1140 kg/m 3 ), high water holding capacity (59.6%), air-filled porosity (7.82%) and hydraulic conductivity (965 mm/h). Four different biofilter assemblies, with vegetated and non-vegetated systems, were examined for several artificial rain events (un-spiked and metal-spiked). Results from un-spiked artificial rain events suggested that concentrations of most of the chemical components in effluent were highest at the beginning of rain events and thereafter subsided during the subsequent rain events. Biofilter growth substrate showed superior potential over garden soil to retain metal ions such as Al, Fe, Cu, Cr, Ni, Zn, Cd and Pb during metal-spiked rain events. Significant differences were also observed between non-vegetated and vegetated biofilter assemblies in runoff quality, with the latter producing better results.